An Evaluation of Determinants Influencing Employee Adherence to Personal Protective Equipment (PPE) Usage in Mitigating Occupational Accident Risks within a Manufacturing Firm in Batam - Mulyana, Andi Erna; Sinaga, Ledy Bagindayana (Journal of Applied Business Administration, 2024)
This study aims to examine the factors influencing employee adherence to the use of Personal Protective Equipment (PPE) within a private manufacturing company in Batam. The study population consists of all production department employees at the company, totaling 87 respondents. A quantitative research design was employed, utilizing a cross-sectional approach and correlation analysis. The relationship between independent variables"”age, tenure, knowledge, availability of PPE, and HSE supervision"”and the dependent variable of PPE compliance was assessed using the chi-square test in SPSS 24. The findings indicate that age, tenure, PPE availability, and HSE supervision do not significantly influence or correlate with employee PPE compliance. In contrast, the knowledge variable demonstrates a significant influence on PPE compliance among employees.